Some aspects of morphogenesis of diabetic encephalopathy - V. A. Tumanskiy; Yu. N. Avramenko (Zaporožskij Medicinskij Žurnal)
On the basis of the literary data and conducted large-scale research it was ascertained that diabetes mellitus raises the risk of cerebral stroke in 2-6 times, the risk of transitional ischemic attacks in 3 times in comparison with the same risk in the general population [3]. Diabetic encephalopathy in its pure form can be found in 80.7% of patients with diabetes mellitus of the 1st type, its development is caused mainly by ineffective metabolic control of autoregulation of cerebral blood flow [4]. Mixed encephalopathy is prevailed among patients with diabetes mellitus of the 2nd type; lacunar heart attack is more often developed among this category of patients [5], multiple focus of ischemic affection of white substance – leukoaraiosis regarded as the areas of increased level of water, gliosis, and demyelination of white substance is often registered [6].